Evaluation of the efficiency of removing sanitary indicators in the process of biological wastewater treatment - Iwona Beata Paśmionka (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: The aim of the study was to assess the effectiveness of biological wastewater treatment in the process of eliminating sanitary indicators at the Biological Sewage Treatment Plant in Piwniczna Zdrój.